Using analytical hierarchy process to rank takaful companies based on health takaful product / Noor Hafizah Zainal Aznam ... [et al.] - Zainal Aznam, Noor Hafizah; Abu Bakar, Wan Asma'; Farhan Zakaria, Shahida (2015)
Most studies evaluate the performance of conventional insurance companies based on cost or profit efficiency. The same approach was taken in evaluating the performance of takaful companies. To use the conventional approach to evaluate Islamic entities is like putting a square peg in a round hole . Hence, the objective of this study is to propose a new model, which will incorporate the objectives of Shariah, that is to protect the interest of the company and public , in assessing the performance of takaful companies. This new approach will account for the interests of the companies, participants and the shareholders. It will also measure the contributions made by the companies to the society. Possible factors include the company' s cost and profit efficiencies ; the customers' level of trust in the company ; innovative financial instruments; preservation of the company's and customers' interests; and the company's corporate social responsibility. Due to voluminous work involved , we proposed to start with a rank of the companies ' innovative financial instruments. We aim to answer WHY selected takaful products are included in the model and HOW effective is the model in ranking the performance of takaful companies .